Contribution to a Critical Study of Transition Theory and Practice - Stanojević, Nenad M. (Sociološki pregled, 2019)
The paper deals with the monograph of Dr Ljubiša Mitrović In the Jaws of Transition: Between the Downfall and the Alternative (A Plea for the Transition of Transition and Alternative Society). First, the structure of the monograph is outlined, as well as author’s basic theoretical starting points. Then, the impact of applying a neo-liberal development strategy on transition societies is discussed, as well as the possibility of establishing an alternative development strategy. Finally, the role and position of the social sciences, humanities and intellectuals in the contemporary world is problematized.
Keywords: transition; neoliberalism; social democracy